UJI AKTIVITAS ANTIOKSIDAN LOTION DARI FRAKSI ETANOL DAUN NIPAH (Nypa fruticans Wurmb.) - Husnani, Husnani (Jurnal Komunitas Farmasi Nasional, 2025)
The skin is the outermost part of the body and is vulnerable to damage caused by free radicals. One way to protect the skin is through topical preparations such as lotion containing natural antioxidants. This study aimed to determine the antioxidant activity of lotion containing the ethanol fraction of nipah leaves and to identify its IC₅₀ value as an indicator of potency. The ethanol fraction was obtained by maceration and liquid-liquid fractionation, and formulated into three lotion variants with different cetyl alcohol concentrations. Antioxidant activity was tested using the DPPH method and analyzed by UV-Vis spectrophotometry. The results showed that the lotion formula with the highest cetyl alcohol concentration (F3) had an IC₅₀ value of 45.39 µg/mL, categorized as very strong. The conclusion is that lotion with ethanol fraction of nipah leaves has high antioxidant activity and potential as a natural cosmetic product.